2012
DOI: 10.1111/j.1540-4560.2012.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Work–Family Guilt and Pro‐ and Anti‐Social Work Behavior

Abstract: This article explores the behavioral outcomes of an understudied emotion, guilt, in the context of the work–family domain. Specifically, we propose that work–family guilt motivates both pro‐ and anti‐social behaviors in the workplace. Working undergraduate students in the United States completed qualitative and quantitative indicators of behavioral responses to work–family guilt. Results demonstrated that when individuals experienced family‐to‐work guilt, they responded with helping behaviors directed toward i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…In one particular instance, the interviewee was quite emotional and sounded deeply touched by the supervisor's behavior when she was describing her supervisor's kindness and understanding, and the need to reciprocate him. This behavior is similar to Morgan and King's (2012) finding that individuals who experience family-to-work guilt respond by engaging in prosocial work behavior, although in our study the prosocial work behavior was toward the supervisor rather than a colleague. Such appreciation and reciprocation of a supervisor's understanding of FIW conflict reflect the high-power distance characteristic of an Eastern culture.…”
Section: Negotiation At Worksupporting
confidence: 88%
See 1 more Smart Citation
“…In one particular instance, the interviewee was quite emotional and sounded deeply touched by the supervisor's behavior when she was describing her supervisor's kindness and understanding, and the need to reciprocate him. This behavior is similar to Morgan and King's (2012) finding that individuals who experience family-to-work guilt respond by engaging in prosocial work behavior, although in our study the prosocial work behavior was toward the supervisor rather than a colleague. Such appreciation and reciprocation of a supervisor's understanding of FIW conflict reflect the high-power distance characteristic of an Eastern culture.…”
Section: Negotiation At Worksupporting
confidence: 88%
“…In contrast, nonfamily‐supportive supervisors might exacerbate WFC and negative employee outcomes. For example, Morgan and King (2012) show how individuals who experience work‐to‐family guilt might respond by shirking work responsibilities. Therefore, we recommend that supervisors be open to negotiations aimed at minimizing WFC to avoid antisocial behavior directed at the organization (e.g., absenteeism).…”
Section: Discussionmentioning
confidence: 99%
“…While being a good father is generally not perceived as incompatible with work or a career, research clearly demonstrates ambivalence toward working mothers (e.g., Greenberger et al, 1988 ; Heilman and Okimoto, 2008 ; King, 2008 ). Normative expectations for being a good parent are often internalized, with feelings of ‘work-family guilt’ when parents violate these normative expectations ( Morgan and King, 2012 ). As a result, working mothers tend to report higher feelings of family-to-work conflict whereas men tend to report higher work-to-family conflict as a meta-analysis by Byron (2005) has shown.…”
Section: Discussionmentioning
confidence: 99%
“…MacDermid et al [190] argued that the role of emotion elicited from WFC on an individual's behavior would be better understood by bringing gender into the work-family conflict issue. Morgan and King [191] found that if an individual faces work-to-family guilt, she reduces her work responsibility, whereby a gender-role orientation plays a moderating role in such responses.…”
Section: Figure 2 Selection Of Parametersmentioning
confidence: 99%